2020
DOI: 10.1111/poms.13176
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Implications of Confirmation Bias‐Inducing Advertising

Abstract: Confirmation bias, a well‐established behavioral anomaly, asserts that when product experience is ambiguous, it is assimilated consistent with expectations set up by prior advertising. In this paper, we combine a strategic model with laboratory experiments to study the effects of consumers’ confirmation bias on firms’ advertising and pricing strategies and its implications for firms’ profits. Our results suggest that confirmation bias does not improve firms’ profits in the short run. However, it confers benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Du et al (2019) consider that entrants are biased in estimating the incumbent's repositioning ability and study how the decision bias influences the equilibrium outcomes. From a consumer perspective, Bagchi et al (2020) study the effects of consumers' confirmation bias on firms' advertising and pricing strategies and the associated profits. While decision biases often mean deviations from the rational behaviors for firms, the studies above show that in complex settings they do not necessarily lead to a worse performance, and can be beneficial in some cases.…”
Section: Decision Biasesmentioning
confidence: 99%
“…Du et al (2019) consider that entrants are biased in estimating the incumbent's repositioning ability and study how the decision bias influences the equilibrium outcomes. From a consumer perspective, Bagchi et al (2020) study the effects of consumers' confirmation bias on firms' advertising and pricing strategies and the associated profits. While decision biases often mean deviations from the rational behaviors for firms, the studies above show that in complex settings they do not necessarily lead to a worse performance, and can be beneficial in some cases.…”
Section: Decision Biasesmentioning
confidence: 99%
“…In addition, results revealed that the abnormal negotiation volume and the standard deviation of abnormal trading volume are significantly higher for new authorities with better readability, which suggest that investors respond to the news more readable to the authorities with more trading behavior. Bagchi et al (2020) investigated the impact of consumers' confirmation bias on firms' advertising and pricing strategies and its implications for firms' profits. Findings revealed that confirmation bias improve firms' profits in the longer time horizon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars study the role of advertising, for example, Zhang (2006), Mian et al (2018), Ivaldi and Muller‐Vibes (2018), Eliaz and Spiegler (2020), Bagchi et al (2020), Chernonog (2020), and Schroeder et al (2021). Trabucchi et al (2017) explain why advertising is typically applied by a platform and their results highlight that the platform advertises to capture the information of the consumers, and then leverage this information to provide customized advertising.…”
Section: Related Literaturementioning
confidence: 99%